The protein corona reduces the anticancer effect of graphene oxide in HER-2-positive cancer cells. Issue 18 (30th August 2022) - Cui, Lishan; Quagliarini, Erica; Xiao, Siyao; Giulimondi, Francesca; Renzi, Serena; Digiacomo, Luca; Caracciolo, Giulio; Wang, Junbiao; Amici, Augusto; Marchini, Cristina; Pozzi, Daniela
Abstract : Schematic representation of the protein corona impact on GO anticancer effect. Abstract : In the last decade, graphene oxide (GO)-based nanomaterials have attracted much attention for their potential anti-cancer properties against various cancer cell types. However, while in vitro studies are promising, following in vivo investigations fail to show any relevant efficacy. Recent research has clarified that the wide gap between benchtop discoveries and clinical practice is due to our limited knowledge about the physical–chemical transformation of nanomaterials in vivo . In physiological environments, nanomaterials are quickly coated by a complex dress of biological molecules referred to as the protein corona. Mediating the interaction between the pristine material and the biological system the protein corona controls the mechanisms of action of nanomaterials up to the sub-cellular level. Here we investigate the anticancer ability of GO in SK-BR-3 human breast cancer cells over-expressing the human epidermal growth factor receptor 2 (HER-2), which is functionally implicated in the cell growth and proliferation through the activation of downstream pathways, including the PI3K/AKT/mTOR and MAPK/ERK signaling cascades. Western blot analysis demonstrated that GO treatment resulted in a marked decrease in total HER-2, associated with a down-regulation of the expression and activation of protein kinase B (AKT) and extracellular signal-regulated kinase (ERK) thus indicating that GO may act as a potent HER-2 inhibitor. On the other side, the protein corona reverted the effects of GO on HER-2 expression and molecular downstream events to the control level. Our findings may suggest a mechanistic explanation of the reduced anticancer properties of GO-based nanomaterials in vivo. These results may also represent a good prediction strategy for the anticancer activity of nanomaterials designed for biomedical purposes, reaffirming the necessity of exploring their effectiveness under physiologically relevant conditions before moving on to the next in vivo studies.